Comparison of culture and polymerase chain reaction techniques in the identification of Tannerella forsythia in periodontal health and disease, an in vitro study - Praveen Kumar Bankur; Aarati Nayak; Kishore Bhat; Rashmi Bankur; Reshma Naik; Nami Rajpoot (Wolters Kluwer Medknow Publications, 2014)
Background and Objectives: Various bacterial species from subgingival biofilm have demonstrated aetiological relevance in the initiation and progression of periodontitis. The aim of this study was to detect the presence of Tannerella forsythia (Tf) in subgingival plaque of periodontally healthy subjects and chronic periodontitis patients by using both culture and PCR technique and compare the two techniques. Materials and Methods: Pooled subgingival plaque samples were taken using sterile curettes from predetermined sites in 50 periodontally healthy subjects and from 50 periodontitis subjects. Samples were analyzed for the presence of T. forsythia using both techniques. Statistical analysis of the results was done using Chi-square test, sensitivity, and specificity tests. Results: Both techniques could detect T. forsythia in subgingival plaque samples from healthy and periodontitis subjects. Periodontally healthy individuals and individuals with chronic periodontitis using the culture technique showed the presence of T. forsythia in 14 and 34%, respectively. PCR technique showed the presence of T. forsythia in 20% healthy and 40% chronic periodontitis patients. T. forsythia detection in the periodontitis group was statistically significantly higher when compared to the healthy group by both culture and PCR technique (P = 0.019 and P = 0.029). PCR demonstrated high sensitivity and low specificity when compared to the culture technique. Conclusion: The results indicated that T. forsythia was more prevalent in periodontitis patients when compared with healthy subjects. The PCR was found to be more sensitive than culture technique for detection of T. forsythia from the subgingival plaque samples.